Co-effects of matrix low elasticity and aligned topography on stem cell neurogenic differentiation and rapid neurite outgrowth. Issue 19 (28th April 2016) - Yao, Shenglian; Liu, Xi; Yu, Shukui; Wang, Xiumei; Zhang, Shuming; Wu, Qiong; Sun, Xiaodan; Mao, Haiquan
Abstract : A hierarchically aligned fibrillar fibrin hydrogel mimics both the soft and oriented features of nerve tissue, thus providing hybrid biophysical cues to instruct cell behavior in vitro and in vivo . Abstract : The development of novel biomaterials that deliver precise regulatory signals to direct stem cell fate for nerve regeneration is the focus of current intensive research efforts. In this study, a hierarchically aligned fibrillar fibrin hydrogel (AFG) that was fabricated through electrospinning and the concurrent molecular self-assembly process mimics both the soft and oriented features of nerve tissue, thus providing hybrid biophysical cues to instruct cell behavior in vitro and in vivo . The electrospun hydrogels were examined by scanning electron microscopy (SEM), polarized light microscopy, small angle X-ray scattering assay and atomic force microscopy (AFM), showing a hierarchically linear-ordered structure from the nanoscale to the macroscale with a soft elastic character (elasticity ∼1 kPa). We found that this low elasticity and aligned topography of AFG exhibit co-effects on promoting the neurogenic differentiation of human umbilical cord mesenchymal stem cells (hUMSCs) in comparison to random fibrin hydrogel (RFG) and tissue culture plate (TCP) control after two week cell culture in growth medium lacking supplementation with soluble neurogenic induction factors. In addition, AFG also induces dorsal root ganglion (DRG) neurons to rapidly project numerous long neurite outgrowths longitudinally along the AFG fibers for a total neurite extension distance of 1.96 mm in three days in the absence of neurotrophic factor supplementation. Moreover, the AFG implanted in a rat T9 dorsal hemisection spinal cord injury model was found to promote endogenous neural cell fast migration and axonal invasion along AFG fibers, resulting in aligned tissue cables in vivo . Our results suggest that matrix stiffness and aligned topography may instruct stem cell neurogenic differentiation and rapid neurite outgrowth, providing great promise for biomaterial design for applications in nerve regeneration.